Inherit the wind - Kramer, Stanley; Douglas, Nathan E.; Smith, Harold Jacob, 1912-1970.; Tracy, Spencer, 1900-1967.; March, Fredric, 1897-1975.; Kelly, Gene, 1912-1996.; York, Dick, 1928-1992.; Anderson, Donna, 1939-; Morgan, Harry, 1915-2011.; Lawrence, Jerome, 1915-2004.; Lee, Robert Edwin, 1918-1994.; United Artists Corporation; et al. (Santa Monica, CA : Metro-Goldwyn-Mayer Studios : Distributed by MGM Home Entertainment, 2004)
A small Tennessee town gained national attention in 1925 when a biology schoolteacher was arrested for violating state law and teaching Darwin's theory of evolution in the classroom.
DVD, widescreen presentation; Dolby digital, mono.
Soundtracks and optional subtitles available in English, French or Spanish.
Spencer Tracy, Fredric March, Gene Kelly, Dick York, Donna Anderson, with Harry Morgan.
Videodisc release of the 1960 motion picture.
Based upon the play by Jerome Lawrence and Robert E. Lee.
Not rated.
Keywords: Scopes, John Thomas; Evolution (Biology) -- Drama; Teaching -- Drama; Teachers in motion pictures; Feature films; Video recordings for the hearing impaired